Inovasi Menuju Transformasi Digital dalam Pelayanan Publik Kajian Sistem Manajemen Pelayanan Desa (SIMPEDA) di Desa Balung Lor - Cahya Ningtyas, Vella Nur; Angin, Ria (Indonesian Journal Publisher, 2023)
Digital transformation is largely seen as a cultural shift that changes the way governments work, communicate, and deliver services, but can also have far-reaching implications, including changing organizational structures and cultures. One of the efforts made by the Jember Regency Government to innovate in digital transformation is by launching the SIMPEDA (Village Service Management System) application for villages in Jember Regency, one of which is Balung Lor Village. This research aims to describe the service transformation process before and after the existence of SIMPEDA in Balung Lor Village. This research uses a qualitative descriptive research method by collecting data through interviews, observation and documentation. The results of the research show that the implementation of the SIMPEDA innovation has gone very well in Bakung Lor Village and they have benefited from this innovation even though there are also negative impacts. Apart from that, according to the study findings, researchers found weaknesses. The theory put forward by Rogers does not cover innovation culture. Rogers' theory does not explain how innovation culture also requires changes in behavior in providing services from manual to digital-based.